The financial crisis and the regulation of credit rating agencies: A European banking perspective - Siegfried Utzig (Asian Development Bank Institute (ADBI), 2010)
Credit rating agencies (CRAs) bear some responsibility for the financial crisis that started in 2007 and remains ongoing. This is acknowledged by policymakers, market participants, and by the agencies themselves. It soon became clear that, given the depth of the crisis, CRAs would not be able to satisfy policymakers by eliminating flaws in their rating methods and improving corporate governance. Although the CRAs were more or less unregulated before the outbreak of the financial crisis, after the crisis started, politicians became increasingly vocal in demanding regulation. Initially, these demands were confined to a more binding form of self-regulation. But as the crisis progressed, the calls for state regulation grew ever louder. It became apparent after the November 2008 G-20 summit in Washington that state regulation could no longer be avoided. In Europe, the course had been set in this direction even before then. Since European policymakers saw the crisis as evidence that the Anglo-Saxon approach to the financial markets had failed, they believed they were now strongly placed to have a decisive influence on shaping a new international financial order. It is remarkable to note the shift in European policy from a self-regulatory approach, which was comparatively liberal in international terms, to quite rigorous state regulation of CRAs. Both the European Commission and the European Parliament drew up far-reaching plans. Although European policymakers knew that only globally consistent regulation would be appropriate for a new world financial order, their initial draft legislation was geared more toward stand-alone European regulation. While the final version of the European Union Regulation on Credit Rating Agencies focuses firmly on the European arena, the key point for all market participants is that this is unlikely to have an adverse effect on the global ratings market. It must nevertheless be recognized that the scope of the selected regulatory approach is extremely narrow. Certainly, it has the potential to improve the corporate governance of CRAs and prevent conflicts of interests. But it can do nothing to address the repeated calls for greater competition or for CRAs to be made liable for their ratings.
Keywords: G01; G18; G21; G24; 330; Finanzmarktkrise; Kreditrisiko; Ratingagentur; Regulierung; Bankgeschäft; Europa